Ghanaian Journalists and Public Relations Practitioners’ Perceptions of Each Other - Forson, E.A. (University Of Ghana, 2013)
This research examined the perceptions journalists and public relations practitioners had of each other in Ghana. Journalists and public relations practitioners were randomly sampled from the membership lists of the Ghana Journalists Association (GJA) and Institute of Public Relations (IPR), Ghana respectively. A total of 220 questionnaires were sent out, 110 to each group. One hundred and fifty-nine (159) usable questionnaires were analyzed in this study. The coorientation approach was used to determine the relationship between journalists and PR practitioners. Generally, the survey indicated some similarities and differences in perceptions on various aspects of their interactions. A significant number of respondents believed journalists and PR practitioners had a cordial relationship. With regard to whether the PR practitioner was trusted, majority of the respondents, both journalists and PR practitioners, responded in the affirmative. The data collected, however, suggested that PR practitioners and journalists disagreed with each other that PR materials were necessary to the production of news. PR practitioners believed strongly that the information they provided journalists made it possible for the latter to perform their duty satisfactorily. Journalists, however, felt strongly that PR materials did not improve the quality of the news product.
M.A.
Keywords: Journalist; Public Relations; Perceptions; Information; Ghana